The Influence of Service Quality, Company Image and Customer Relationship on Customer Satisfaction Expedition in Sidoarjo Regency: Pengaruh Kualitas Layanan, Citra Perusahaan dan Customer Relationship Terhadap Kepuasan Konsumen Ekspedisi di Kabupaten Sidoarjo - Kurniawan, Ari Lista; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2022)
The results showed that: Service Quality affects Consumer Satisfaction of J&T express delivery. Kurniawan, Ari Lista. 2022. Effect of Service Quality, Company Image and Customer Relationship on Consumer Satisfaction of J&T Express Expedition Sidoarjo Regency. This study aims to determine the influence of Service Quality, Company Image and Customer Relationship on Consumer Satisfaction. This research a quantitative approach . Sampling in the study used accidental sampling techniques, with a total of 96 respondents from J&T Express Expedition consumers . Data collection techniques using questionnaires distributed throughquestionnaires. . Data analysis in this study includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, linearity test, auto correlation test, multiple linear regression analysis, T test, multiple correlation coefficient (R) and coefficient of determination (R2). Data processing in this study used the SPSS 22 (Statistical Program For the Social Sciences) software program. The results of the study indicate that service quality has an effect on consumer satisfaction with J&T express delivery. Company Image has an effect on customer satisfaction with J&T express delivery. Customer relationship hasan effect on customer satisfaction with J&T express delivery.